Pola Penggunaan Bahan Alam sebagai Pengobatan Tambahan Antihipertensi di Puskesmas Pancasan pada Tahun 2024 - KALIGIS, CLAUDIA; YUNITA, FENNY (Hang Tuah Medical Journal, 2025)
Hypertension is one of the main causes of death rates in Indonesia. This condition is characterized by systolic blood pressure ≥140 mmHg and diastolic ≥90 mmHg. According to WHO, recommended conventional drug therapy includes diuretics, angiotensin receptor blockers (ARB), angiotensin converting enzyme inhibitors (ACEI), and long-acting dihydropyridine calcium channel blockers. A number of studies have shown that several natural ingredients commonly consumed daily have potential as antihypertensives. These natural ingredients include garlic (Allium sativum), celery (Apium graveolens), and cucumber (Cucumis sativus). Based on the 2023 Indonesian Health Survey, the proportion of utilization of traditional health efforts in Indonesia was 32,5% and the proportion of utilization of family medicine gardens (TOGA) was 10%. This study aims to evaluate the pattern of use of natural antihypertensive ingredients in hypertensive patients seeking treatment at the Pancasan Community Health Center in December 2024. The research method was cross-sectional descriptive observation with a total of 110 hypertensive patients as respondents. Data was collected through interviews and filling out questionnaires and presented descriptively. The characteristics of the majority of respondents are women with an age range of 41-50 years and the duration of suffering from hypertension is classified as long term. The research results showed that as many as 106 out of 110 patients consumed natural antihypertensive ingredients. The most widely used natural ingredient is cucumber, namely 36.40%, with the most common method of use being direct consumption.